Valuing crisis, acceptance of illness and social support among people suffering from lung cancer - Mącik, Dorota; Fijałkowska, Sylwia; Nycz, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2011)
Introduction : For people suffering from cancer the psychological problems are equally severe as those of somatic nature. This type of illness dramatically affects the basis of their existence and their value system. In order to return to a psychological balance it is vital to have support from people around them and to accept the illness at least at a level at which the patient is motivated for treatment. The aim of this study was to determine whether people suffering from lung cancer are more affected by their value crisis, what the level of their acceptance of the illness is, and what type of public support they receive in comparison to people suffering from other lung diseases. Material and methods: The study was conducted on 50 individuals (28 women, 22 men), of whom 25 had lung cancer and 25 suffered from a different lung disease (in both groups there were 14 women and 11 men). In the study the following instruments were used: Questionnaire to Investigate the Crisis of Value System (KKW), Acceptance of Illness Scale (AIS) and Scale of Social Support (SWS). The study was conducted between February and March 2010 at the pulmonological ward of a hospital. Results : The results of the study show that people suffering from lung cancer have a more severe value crisis and accept their illness at a lower level compared to controls. Nevertheless, the study did not confirm the thesis that people suffering from lung cancer receive more valuing and emotional support than those with other lung diseases.